Industri Kreatif Kearifan Lokal Kerajinan Limbah Pelepah Pinang Masyarakat Pinggiran - Hertati, Lesi; Puspitawati, Lilis; Gantino, Rilla; Ilyas, Meifida (UKInstitute, 2021)
One of the betel nut plate craftsmen who is also the Chairperson of the Mendis Maju Bersama (MMB) Cooperative, Supriyanto, admits that he produces pinan midrib plates. Farmers in Bayung Lencir, South Sumatra, burn areca nuts. But now, the betel nut is used by residents to become a handicraft that has a selling value. To produce cutlery from areca nut, the residents use a press machine. Betel nuts are washed before processing. The old fronds are then dried. After drying, the fronds are pressed and then cut to the size of the plate or rice box. Before printing, the fronds must be moistened first so that they are softer and do not tear easily. Creative industry and environmentally friendly product innovation will be the focus of the development of betel nut midrib management. Availability of raw materials and empowering sustainable communities because this product addresses environmental issues, especially the issue of the use of plastics in Indonesia so far and this product is one of the solutions to product innovation in the areca nut substitute for plastic and styrofoam. The results of innovation in the management of areca nut as a substitute for Styrofoam are the handicrafts of rural communities in order to support the family economy and maintain an environmentally friendly nature.Abstrak: Salah satu pengerajin piring pelepah pinang yang juga Ketua Koperasi Mendis Maju Bersama (MMB), Supriyanto mengaku produksi piring pelepah pinan. Pelepah pinang biasanya dibakar oleh para petani di Bayung Lencir, Sumsel. Namun kini, pelepah pinang dimanfaatkan warga untuk menjadi kerajinan yang punya nilai jual. Untuk memproduksi peralatan makan dari pelepah pinang warga menggunakan mesin press. Pelepah pinang dicuci bersih sebelum diolah. Pelepah tua kemudian dikeringkan. Setelah kering, pelepah di-press lalu dipotong sesuai ukuran piring atau kotak nasi. Sebelum cetak, pelepah harus dibasahi dulu agar lebih lembut dan tidak mudah robek. Industri kreatif dan inovasi produk ramah lingkungan akan menjadi fokus pengembangan pengelolaan pelepah pinang Ketersediaan bahan baku serta memberdayakan masyarakat berkelanjutan karena produk ini menjawab isu lingkungan khususnya isu Pegunaan Plastik Di Indonesia selama ini dan produk ini salah satu solusinya inovasi produk pelepah pinang penggganti plastik dan styrofoam Produk hasil inovasi pengelolaan pelepah pinang menjadi wadah makanan pengganti styrofoam adalahhasil kerajinan tangan masyarakat pinggiran guna menopang ekonomi keluarga serta menjaga alam yang ramah lingkungan.